The Effect of Prosecutorial Actions on Deterrence: A County-Level Analysis. (May 2020) - Mourtgos, Scott M.; Adams, Ian T.
In the current study, we examine prosecutorial decisions that affect the certainty, celerity, and severity of punishment at the county level in the state of Florida. Leveraging a unique data set, we investigate the effect of the rate at which prosecuting agencies within each county filed formal charges against offenders (certainty), the swiftness of criminal case resolution (celerity), and the rate at which cases were pled to less severe punishments (severity). We test for the effect of those covariates on aggregate county-level crime rates over a 5-year period. We find that prosecutors' effect on the certainty and celerity of punishment was associated with lower levels of crime, whereas their effect on the severity of punishment was not. Together, these findings highlight the role of the prosecutor in shaping the general deterrent environment within a county.